-4(5x-9)=6(2x+5)

Simple and best practice solution for -4(5x-9)=6(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5x-9)=6(2x+5) equation:



-4(5x-9)=6(2x+5)
We move all terms to the left:
-4(5x-9)-(6(2x+5))=0
We multiply parentheses
-20x-(6(2x+5))+36=0
We calculate terms in parentheses: -(6(2x+5)), so:
6(2x+5)
We multiply parentheses
12x+30
Back to the equation:
-(12x+30)
We get rid of parentheses
-20x-12x-30+36=0
We add all the numbers together, and all the variables
-32x+6=0
We move all terms containing x to the left, all other terms to the right
-32x=-6
x=-6/-32
x=3/16

See similar equations:

| 4x−2​(x−3​)=−4+5x−8 | | 4x+2+75+63=180 | | 8f+9f=32 | | -6x^2-18+60=0 | | 8/1x-2=6 | | 1/2(6x+10)=13 | | 4x+5-2x-2=3x-3×-3 | | 1x–5=5–9x | | 25+3x=115 | | 4|-4x+9|=21 | | 9x*2+25=0 | | -2x-1=5x+8 | | 2x+8+3x+19=7x+5 | | 2v+4=-1    | | 12x-19x= | | 18.753n=18.75 | | 7x+5+3x+19+2x+8=180 | | 2(n^2+n)=5n | | 10-4x-1+6x=-11 | | N=4x | | -5(-4+4x)=120 | | -7=b-6 | | 0=6x^2+18-60 | | -9x+19+x+23=2 | | Y=1-4(m/2) | | 9x+18+5x+20+44=180 | | 3x+19+7x+5=2x+8 | | 7-1.5d0.5(7d+4)=7−1.5d | | -10-12=5m | | {x}{5}+5=10 | | 19x15=x | | 16x+46=-7x^2 |

Equations solver categories